Polarisasi, Relasi Media, dan Narasi Publik pada Kontestasi Politik Menjelang Pilpres 2024 di Platform X - Harry Setiawan; Muslikhin Muslikhin; Eka Fitri Qurniawati; Dafrizal Samsudin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Kata